Nutrition: The position in English to-day - M'Gonigle, G. C. M. (George Cuthberth Mura), -1939 (London : Industrial Christian Fellowship)
1936-11 1936 1930s 15 pages produce is entitled to a fair return on his capital and labour, but schemes which increase the price of essential foods, such as milk, butter, eggs, cheese, fish, meat, vegetables and fruit, or limit their production, are contrary to the demands of social justice, and cannot but be reflected in decreased consumption, by the poor, of foods of which they already have too little. Whether prices be reduced or purchasing power increased matters little to the scientist, who shows the evil to be present. It is for the public conscience to determine how to get to those who lack good food the surplus (whether actual or potential) which exists. The scientist can point to the existing state of affairs, he can even suggest remedies, but he cannot put the remedial methods into effect. That is the task of the people moved to action by the stirring of its conscience, and its determination that the unemployed and the poorly paid shall find within their reach a sufficiency of the protective foods, to enable them to conserve the only form of capital they possess, namely, their bodily health. 15X/2/217/2